Pharmacologic management of HR+/HER2− mBC: a clinically oriented review - Chiru, Elena Diana; Sojak, Lina; Landin, Julia; Vetter, Marcus; Grašič Kuhar, Cvetka (Frontiers in Oncology, 2025)
Breast cancer (BC) remains the most prevalent cancer among women worldwide, with hormone receptor-positive (HR+) and human epidermal growth factor receptor 2-negative (HER2-) subtypes representing approximately 75% of cases. Endocrine therapy (ET) has been foundational in HR+ BC treatment, significantly reducing recurrence and mortality rates, yet resistance to ET remains a critical challenge, particularly in the metastatic setting. Recent treatment advancements—especially CDK4/6 inhibitors (CDK4/6i) in first-line therapy, have reshaped management of HR+ HER2- mBC. Additionally, novel agents like selective estrogen receptor degraders (SERDs) and proteolysis-targeting chimeras (PROTACs), have proven to be effective against ER-resistance inducing mutations, such as ESR1, while poly ADP-ribose polymerase inhibitors (PARPi) showed targeted benefit in BRCA-mutated tumors. In breast cancer expressing AKT/PIK3CA pathway alterations, drugs like alpelisib, capivasertib, and inavolisib have recently been approved, demonstrating improved PFS in this specific patient population. Recent developments of antibody-drug conjugates (ADCs) have also extended therapeutic options to previously labeled HER2-negative tumors, with drugs like trastuzumab deruxtecan (T-DXd) demonstrating efficacy in newly emerged HER2-low and HER2-ultralow pathologic subgroups, extending median overall survival to almost 2 years. Most of these drugs have paved the way for personalized medicine and opened questions around optimal sequencing of ET and application of combination therapies, which continue to be investigated through clinical trials. This review seeks to highlight current and emerging treatment strategies addressing ET resistance to improve survival outcomes for HR+ mBC patients, emphasizing the need for personalized approaches.